Capacitive deionization of NaCl from saline solution using graphene/CNTs/ZnO NPs based electrodes. (28th August 2019) - Arora, Naman; Banat, Fawzi; Bharath, G; Alhseinat, Emad
Abstract: Capacitive deionization (CDI) is an energy efficient and cost-effective technology for electrosorption of salt ions. In this work, graphene/CNTs/ZnO (FGC-ZnO) with different loading of ZnO (5% and 10%) hybrid material was developed and used as high-performance CDI electrode for the removal of NaCl from saline solution. FE-SEM and HR-TEM images confirmed that the hybrid material has interconnected network with well-ordered structure covering ZnO nanoparticles. The FGC-ZnO-10% hybrid material showed enhanced specific capacitance of 280 F g −1 at 10 mV s −1 as compared to FGC-ZnO-5%. Moreover, a high electrosorption capacity of 28.62 mg g −1 in 600 mg l −1 NaCl at 1.2 V was obtained with the FGC-ZnO-10% hybrid material in a batch-mode CDI cell. The Kim–Yoon plot demonstrated that the maximum achieved ASAR is 1.004 mg g −1 min −1 at 1.2 V. This work suggested that FGC-ZnO-10% material have the potential to be utilized as CDI electrode for the desalination of saline water.